(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This abstract investigates the multifaceted impact of physical fitness and exercise on women across various dimensions of health and well-being. Recognizing the unique physiological, social, and cultural factors that shape women’s experiences with exercise, this study aims to elucidate the diverse benefits, challenges, and implications associated with regular physical activity. Physical fitness and exercise play a crucial role in promoting women’s overall health, encompassing both physical and mental well-being. Engaging in regular exercise has been linked to numerous health benefits for women, including reduced risk of chronic diseases such as cardiovascular disorders, diabetes, osteoporosis, and certain types of cancer. Moreover, exercise contributes to weight management, improves cardiovascular fitness, enhances muscular strength and flexibility, and fosters a positive body image.